PPARγ and PPARδ as Modulators of Neoplasia and Cell Fate - Robert I. Glazer; Hongyan Yuan; Zhihui Xie; Yuzhi Yin (PPAR Research)
PPARγ and PPARδ agonists represent unique classes of drugs that act through their ability to modulate gene transcription associated with intermediary metabolism, differentiation, tumor suppression, and in some instances proliferation and cell adhesion. PPARγ agonists are used by millions of people each year to treat type 2 diabetes but may also find additional utility as relatively nontoxic potentiators of chemotherapy. PPARδ agonists produce complex actions as shown by their tumor promoting effects in rodents and their cholesterol-lowering action in dyslipidemias. There is now emerging evidence that PPARs regulate tumor suppressor genes and developmental pathways associated with transformation and cell fate determination. This review discusses the role of PPARγ and PPARδ agonists as modulators of these processes.